2014
DOI: 10.3109/17549507.2014.941935
|View full text |Cite
|
Sign up to set email alerts
|

Pharyngeal transit in patients with chronic progressive external ophthalmoplegia

Abstract: It was concluded that patients with CPEO have shorter pharyngeal transit duration of paste and solid boluses than normal volunteers, which may be a consequence of a spontaneous smaller bolus volume in each swallow and/or effortful swallows.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
1
0
4
Order By: Relevance
“…En la miopatía mitocondrial se afecta gravemente la estructura y función del músculo esquelético por el malfuncionamiento de la fosforilación oxidativa (7,11) . Las fibras musculares tipo 1 se caracterizan por la resistencia a la fatiga y poca fuerza.…”
Section: Discussionunclassified
See 3 more Smart Citations
“…En la miopatía mitocondrial se afecta gravemente la estructura y función del músculo esquelético por el malfuncionamiento de la fosforilación oxidativa (7,11) . Las fibras musculares tipo 1 se caracterizan por la resistencia a la fatiga y poca fuerza.…”
Section: Discussionunclassified
“…Estos pacientes son particularmente susceptibles a tener neumonía, dada la presencia concurrente de debilidad laríngea, tos inefectiva por cierre incompleto de la glotis, alteración del tono y la presión del esfínter esofágico superior y alteración del tránsito faríngeo y esofágico, todo lo cual conduce a fenómenos aspirativos. Los trastornos de la deglución se presentan en el 50 % de los pacientes con CPEO (7,14) . La neumonía es la principal causa de muerte y puede tener un curso más grave que conlleva a la falla ventilatoria y dificultades en el retiro del soporte ventilatorio.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…The authors found progression of dysphagia with age. Fourteen patients with CPEO caused by mtDNA deletion(s) or point mutations were subjected to videofluoroscopy to evaluate the pharyngeal transit of liquid, paste and solid boluses after they were carefully investigated by a speech-language pathologist [68] . Functional evaluation was performed with swallowing 5 mL and free volumes of liquid, paste and solid boluses.…”
Section: Mitochondrial Myopathiesmentioning
confidence: 99%